Renewable Fuels for Internal Combustion Engines - Wierzbicki, Sławomir; Duda, Kamil; Mikulski, Maciej (MDPI, 2021)
The continuous need for systematization and open dissemination of knowledge on Renewable Fuels intended for use in Internal Combustion Engines forms the premise of the presented Special Issue titled “Renewable Fuels for Internal Combustion”. Experts in the field were encouraged to share their latest findings in the form of original research papers, case studies, or short reviews. Works targeting all aspects of the value chain were considered necessary, including the following: (liquid and gaseous) fuel production process, upgrading (catalytic and fractional blending), up to end, valorization in combustion engines (conventional and advanced concepts). Finally, techno-economic analyses aiming to valorize the value chain holistically were warmly encouraged to submit papers in this Special Issue of the Energies Journal. In this book, the reader will find successful submissions that present the latest findings from the discussed research field, encapsulated into nine chapters.
Keywords: Additives for alternative fuels; alternative fuels; Emission characteristics; Engine performance; Engine thermodynamics; Innovative combustion concepts; fi=Energiatekniikka|en=Energy Technology|